An initial examination of free and proprietary software-selection in organizations - Sticklen, D.; Issa, Theodora (2013)
© 2013, IGI Global. This article presents the findings of a study concerning organisational software-selection in the context of proprietary and "Free Software". Proprietary software with its inherent benefits and drawbacks remains dominant over Free Software in many business contexts. In contrast, the arrival of disruptive approaches to applying technology, such as cloud-computing, almost certainly mandates a heterogeneous software environment. However, this paper abstracts to the organisational context, as opposed to solely concentrating on the technical aspects, so that broader issues surrounding both proprietary software and Free Software adoption are brought into focus and may provide academics and practitioners with insight into what many would consider an information technology-centric matter. Contemporary multi-disciplinary literature addressing the areas of software-selection methodology, architectures for service delivery, and software types, are combined with recent findings from primary research in order to draw initial conclusions on the current state of software-selection in organisations.